2019
DOI: 10.47114/j.agroped.2018.jun8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evaluation of Land Resources for Management of Barela Village in Seoni district, Madhya Pradesh using High Resolution Satellite Data and GIS

Abstract: The present investigation was carried out in Barela village of Seoni district, Madhya Pradesh to characterize, classify and evaluate the land resources using IRS-LISS-IV and GIS. Five major landforms viz. plateau; escarpments, mound, pediment and alluvial plain were identified and delineated. Based on image characteristics, seven land uses/ land cover classes’ viz., single crop, double crop, degraded forest, wasteland, river, waterbody and habitation were identified. Five slope classes viz., very gently slopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The major limitations of these soil are soil depth, soil fertility and organic carbon. Shweta et al (2010) also reported soil depth as the limitation for the cultivation of cotton, sorghum and soybean in soils of Khapri village of Nagpur district of Maharashtra. Sonegaon soils areclay, moderately alkaline, medium in organic carbon and moderately calcareous in nature.…”
mentioning
confidence: 98%
“…The major limitations of these soil are soil depth, soil fertility and organic carbon. Shweta et al (2010) also reported soil depth as the limitation for the cultivation of cotton, sorghum and soybean in soils of Khapri village of Nagpur district of Maharashtra. Sonegaon soils areclay, moderately alkaline, medium in organic carbon and moderately calcareous in nature.…”
mentioning
confidence: 98%